Rice LEAFY COTYLEDON1 Hinders Embryo Greening During the Seed Development - Guo, Fu; Zhang, Peijing; Wu, Yan; Lian, Guiwei; Yang, Zhengfei; Liu, Wu; Buerte, B.; Zhou, Chun; Zhang, Wenqian; Li, Dandan; Han, Ning; Tong, Zaikang; et al. (Frontiers in Plant Science, 2022)
LEAFY COTYLEDON1 (LEC1) is the central regulator of seed development in Arabidopsis, while its function in monocots is largely elusive. We generated Oslec1 mutants using CRISPR/Cas9 technology. Oslec1 mutant seeds lost desiccation tolerance and triggered embryo greening at the early development stage. Transcriptome analysis demonstrated that Oslec1 mutation altered diverse hormonal pathways and stress response in seed maturation，and promoted a series of photosynthesis-related genes. Further, genome-wide identification of OsLEC1-binding sites demonstrated that OsLEC1 bound to genes involved in photosynthesis, photomorphogenesis, as well as abscisic acid (ABA) and gibberellin (GA) pathways, involved in seed maturation. We illustrated an OsLEC1-regulating gene network during seed development, including the interconnection between photosynthesis and ABA/GA biosynthesis/signalling. Our findings suggested that OsLEC1 acts as not only a central regulator of seed maturation but also an inhibitor of embryo greening during rice seed development. This study would provide new understanding for the OsLEC1 regulatory mechanisms on photosynthesis in the monocot seed development.